Morfologia do sistema reprodutor masculino da lagosta espinhosa Panulirus argus (LATREILE, 1804) (CRUSTACEA: DECAPODA: PALINURIDAE) do litoral do Estado do Ceará - Rodrigues, Francisco Cleyton Lopes (2007)
The fishery of the spiny lobster Panulirus argus, found in the coast of the state of Ceará, has been declining in the last years. Studies about the reproductive aspects of lobsters are still scarce, mainly for the males, needing investigations in the area of reproductive biology. The present study describes the morphology of the male reproductive system of P. argus characterizing histologically and histochemically the somatic and germinative components, aiming to subsidy the regulation of the fishery based in the relationship between the biometric data and physiological maturation of the collected animals. The animals were acquired from fishermen of the Cascavel, Beberibe, Caucaia and Trairí municipalities, in the Ceará coast. The individuals were measured morfometrically and the reproductive organs were submitted to the routine histological procedures (fixation, dehydration, impregnation and embedded in paraffin, sectioned and coloration). It was used 59 males, with the average of total length of 127,49mm. The organization of the reproductive system follows the basic model described for Decapoda, being formed by equal structures, testis, vas deferens and androgenic gland. The gonads were white or transparent and the two testis’s lobes are not connected to each other, differing in this aspect, to some decapods. Animals larger than 155 mm of total length, presented spermatophores in the vas deferens, and were considered in this study, as mature physiologically. The testis of P. argus were covered by a thin layer of fibrous material and presented more internally, an extensive coiled seminiferous tubules, and between the external spaces to the tubules are vessel and hemal sinuses. In the sections of the seminiferous tubules it was possible to differentiate five different stages of the germinative cells: spermatogonia, spermatocytes I and II, spermatids and spermatozoa, considering the size and mainly the distribution of the chromatin in the nucleus. The androgenic gland was not visualized macroscopically and was poorly developed in the analyzed animals. The animals larger than 155mm of total length were physiologically mature, presenting spermatophore in the vas deferens.